MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK - R Nur Alfiatunnisa; Imam Syafe’i; Sunarto Sunarto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low analytical reasoning skills of students, due to the dominance of conventional instructional patterns and the limited space for independent exploration, underlie this study. These operational issues trigger students' systematic failure to formulate logical solutions when facing contemporary academic challenges. The primary focus of this research is to evaluate the effectiveness of the problem-based learning (PBL) model as a curative strategy to boost critical thinking skills in the realm of mathematical reasoning. The research steps were carried out systematically using library research methods on reputable scientific publications from 2020 to 2026. Secondary data processing procedures were executed through document searches in reputable journals, theoretical text reduction, structured narrative presentation, and inductive conclusion drawing. Conceptual findings reveal that the PBL syntax, which emphasizes the presentation of authentic, real-world problem stimulations, has proven reliable in triggering optimal escalation of student mental engagement. This interactive knowledge assimilation process effectively transforms the classroom ecosystem from passive to more collaborative, communicative, and responsive. The main conclusion confirms that the implementation of the problem-based learning model successfully facilitates the development of a resilient, adaptive, and technologically literate independent learner identity. Educators are recommended to develop daily lesson plans that consistently integrate contextual cognitive conflict to stimulate students' intrinsic motivation. ABSTRAK Rendahnya ketajaman nalar analitis siswa akibat dominasi pola instruksional konvensional serta minimnya ruang eksplorasi mandiri melatarbelakangi kajian ini. Masalah operasional tersebut memicu kegagalan sistematis peserta didik dalam merumuskan penyelesaian logis saat menghadapi tantangan akademis kontemporer. Fokus utama penelitian ini adalah mengevaluasi tingkat efektivitas model problem-based learning (PBL) sebagai strategi kuratif untuk mendongkrak kemampuan berpikir kritis dalam ranah penalaran matematika. Langkah-langkah penelitian dijalankan secara sistematis menggunakan metode studi kepustakaan (library research) terhadap publikasi ilmiah tepercaya dalam rentang waktu 2020-2026. Prosedur pengerjaan data sekunder dieksekusi melalui penelusuran dokumen jurnal bereputasi, reduksi teks teoretis, penyajian naratif terstruktur, hingga penarikan kesimpulan induktif. Temuan konseptual menyingkap bahwa sintaks PBL yang menitikberatkan pengajuan stimulasi masalah autentik dunia nyata terbukti andal memicu eskalasi keterlibatan mental siswa secara optimal. Proses asimilasi pengetahuan yang interaktif ini efektif mentransformasikan ekosistem kelas dari pasif menjadi lebih kolaboratif, komunikatif, dan responsif. Simpulan utama menegaskan bahwa implementasi model pembelajaran berbasis masalah sukses memfasilitasi pembentukan identitas pembelajar mandiri yang tangguh, adaptif, serta melek teknologi. Pendidik direkomendasikan menyusun rencana pelaksanaan pengajaran harian yang mengintegrasikan konflik kognitif kontekstual secara konsisten demi memicu motivasi intrinsik anak.